Giant Gartner’s Duct Cyst Mimicking Pelvic Organ Prolapse: A Rare Case Report - Effendy, Citra Utami; Sri Wahyu Maryuni; Veenda Herlyna Pertiwi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Gartner’s duct cysts are benign vaginal cysts originating from embryological remnants. While usually asymptomatic, larger cysts can mimic pelvic organ prolapse, leading to misdiagnosis and delayed treatment. This case emphasizes the importance of accurate diagnosis and appropriate surgical intervention in managing large GDCs. Case presentation: A 43-year-old woman presented with a protruding vaginal mass, initially mistaken for pelvic organ prolapse. Examination revealed a large Gartner’s duct cyst on the posterior vaginal wall. Surgical excision and marsupialization were performed, confirming the diagnosis. Conclusion: This case highlights the importance of thorough evaluation in women presenting with vaginal masses. Large Gartner’s duct cysts, though rare, can mimic pelvic organ prolapse, necessitating accurate diagnosis and appropriate surgical intervention.